Complex Compound with Transitional Metal of Akway Bark (Drimys piperita Hook f.) as Low Molecular Weight Scavenging Antioxidant: a Computational Study: Complex Compound of AkwayBark as Scavenging Antioxidant - Hostalige Hutasoit; Dionysius Joseph Djoko; Sutiman B Sumitro; Simon Bambang Widjanarko (Journal of Tropical Life Science, 2021)
Akway (Drimys piperita Hook f.) was known as an endogenous plant of Indonesia. This plant was investigated as free radical scavenger based on paramagnetic properties. This study aimed to identify the bioactive compound and the role of Fe metals ions to enhance the free radical scavenger capacity as Low molecular weight antioxidant (LWMA) of akway. This study was designed by ultra-performance liquid chromatography (UPLC) coupled with ultra-high-resolution time of flight-mass spectrometry detector (TOF-MS), docking (Pyrex and Discovery Studio 2016 Client) and pharmacokinetic properties prediction (SwissADME). UPLC-TOF-MS analysis showed that herbal akway bark has five molecular formula (C4H3N10O21-, C14H19N4O91-, C4H7N6O51-, C15H28NO31+, and C23H32NO71+). The docking was illustrated the complex binding akway formula with Fe and its role as a metal donor and metal acceptor. It also confirmed on pharmacokinetics properties prediction which molecular compounds of akway have aqueous solubility. It meant the herbal akway bark complexed to Fe could be a low molecular weight antioxidant and it could be escalated free radical scavenger capacity.